Penilaian Kinerja (Performance Assessment) dalam Pembelajaran Bahasa Indonesia di SMP: Kajian Literatur - Suci Raufi Alkarima; Amril Amir; Abudrahman (Lembaga Yasin AlSys, 2026)
Assessing language competence requires an approach capable of evaluating students’ knowledge and skills authentically and holistically. This study aimed to comprehensively examine the concept of performance assessment in Indonesian language instruction at the junior high school level. The study employed a systematic literature review approach by examining various scholarly sources that discuss the nature, types, components, and implementation of performance assessment in language instruction. The findings showed that performance assessment is a relevant authentic assessment method for comprehensively measuring students’ language competence, including listening, speaking, reading, and writing skills. Its implementation still faces several challenges, particularly time constraints, assessor subjectivity, and disparities in teachers’ understanding of how to use assessment rubrics. Performance assessment designed systematically with clear criteria and rubrics can improve assessment validity and reliability, motivate students, and promote more meaningful learning. These findings emphasize the importance of strengthening teachers’ competence in designing and implementing effective performance assessments aligned with curriculum requirements. This review provides a conceptual foundation and practical recommendations for Indonesian language teachers to develop assessments that represent students’ language competence more authentically.